Food politics and development (2020)
Food has become both a pivotal topic in development and a lens through which to integrate and address a range of contemporary global challenges. This review article addresses in particular the interrelationship between food and sustainable, equitable development, arguing that this is fundamentally political. We offer a set of approaches to understanding food politics, each underlain by broader theoretical traditions in power analysis, focused respectively on food interests and incentives; food regimes; food institutions; food innovation systems; food contentions and movements; food discourses, and food socio-natures. Applications of these approaches are then illustrated through a set of problematiques, providing a (selective) overview of some of the major literatures and topics of note in food politics and development. Starting with the role of the state and state-society relations in different forms of food regime, we then consider the role of science and technology (and its discourses) in shaping agricultural and food policy directions before looking in more detail at rural livelihoods in agri-food systems and the politics of inclusive structural transformation. Broadening beyond agri-food systems then brings us to interrogate dominant narratives of nutrition and review literature on the cultural politics of food and eating. A concluding section provides a synthesis across the cases, drawing together the various approaches to power and politics and showing how they might be integrated via an analytical framework which combines plural approaches to describe different pathways of change and intervention, raising critical questions about the overall direction and diversity of these pathways, their distributional effects, and the extent of democratic inclusion in decisions about food pathways. We find this extended ‘4D’ approach helpful in highlighting current food systems inequities and the political options for future food systems change, and conclude by considering how it might be harnessed as part of a future interdisciplinary, engaged research agenda.